The Ghost of a Rating Downgrade : What happens to Borrowing Costs When a Government Loses its Investment Grade Credit Rating? - Hanusch, Marek; Hassan, Shakill; Algu, Yashvir; Soobyah, Luchelle; Kranz, Alexander (World Bank, Washington, DC, 2016)
Since the global financial crisis and the end of the commodity super-cycle, weak growth and countercyclical fiscal policy have contributed to deteriorating public finances in many countries across the globe. As public debt burdens rose, credit ratings deteriorated and a number of countries have been downgraded from investment to sub-investment ('junk') grade. Rating downgrades continue to haunt countries in a world of low growth. This paper examines the effect of such downgrades on short-term government borrowing costs, using a sample of 20 countries between 1998 and 2015. The analysis suggests that a downgrade to sub-investment grade by one major rating agency increased Treasury bill yields by 138 basis points on average. Should a second rater follow suit, Treasury bill rates increase by another 56 basis points (although this effect is not statistically significant). The analysis does not detect any equivalent impacts for local currency ratings, even though T-bills tend to be issued in domestic currency, although this may be due to sample limitations and is therefore not conclusive.